Mycobacterial Spindle Cell Pseudotumor of the Lymph Nodes. (May 2021) - Singh, Balraj; Kaur, Parminder; Majachani, Nicole; Guragai, Nirmal; Gupta, Sachin; Maroules, Michael
Mycobacterial spindle cell pseudotumor (MSP) is characterized by benign proliferation of spindle-shaped histiocytes containing acid-fast Mycobacterium . It is usually seen in immunocompromised patients. Limited literature is available regarding MSP. In this article, we report a case of 36-year-old African American male with past medical history of HIV (diagnosed in 2005), noncompliance who presented with generalized weakness, fever, and dizziness on ambulation and was found to have generalized lymphadenopathy and underwent biopsy of the lymph nodes, which was consistent with MSP.